2019 International Conference on Information Networking (ICOIN) 2019
DOI: 10.1109/icoin.2019.8718189
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Gateway Routing Scheme for Disaster Recovery Scenario

Abstract: Natural disaster can strike at any time and in any place. Once it has occurred, it can ruin large regions, cause damage to houses and buildings, and destroy physical communication infrastructure. Therefore, a network backup is required in the disaster recovery area because victims will want to contact their important person to update the current situation as soon as possible. A mobile ad hoc network (MANET) is a collection of mobile devices that dynamically communicate with each other without any physical infr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Every gateway will take a modest hit thanks to the traffic handling strategy provided by Mahiddin and Sarkar (2019) [48]. In the event that the primary gateway breaks, Minh et al (2014) [49] suggested using an OEMAN technique to designate one mobile device as a backup access point.…”
Section: Related Workmentioning
confidence: 99%
“…Every gateway will take a modest hit thanks to the traffic handling strategy provided by Mahiddin and Sarkar (2019) [48]. In the event that the primary gateway breaks, Minh et al (2014) [49] suggested using an OEMAN technique to designate one mobile device as a backup access point.…”
Section: Related Workmentioning
confidence: 99%
“…Some previous works contribute to solve the congestion of the traffic [8], or highlight the need of organizing a disaster recovery plan for each area [9]. While there are solutions based on the virtualization of cloud services [10], other solutions desegregate the network to minimize equipment failure risks and propose protection approaches for fast recovery of network nodes after disaster happens [11].…”
Section: Current Research On Disaster Recoverymentioning
confidence: 99%
“…Figure 1 MANET operations [3] MANET can be considered as a promising solution, especially in an unfavourable conditions such as disaster response and recovery where fixed infrastructure is unavailable due to the aftermath of the disaster [4]. The communication network can be recovered within a short time, making delays and errors in SAR operations and mission critical to be minimized.…”
mentioning
confidence: 99%
“…The communication network can be recovered within a short time, making delays and errors in SAR operations and mission critical to be minimized. Thus, the MANET can be considered as one of the best approach for SAR operations due to its rapid deployment, making the rescue teams to immediately respond to the victims call for help upon receiving [4,5]. The objectives to focus the current aspects in this area are as under: 1.…”
mentioning
confidence: 99%